2008
DOI: 10.1089/apc.2008.0012
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Increases HDL3–Cholesterol and Decreases Subcutaneous Truncal Fat in Nondiabetic Patients with HIV-Associated Lipodystrophy

Abstract: The purpose of this study was to assess metformin effects on high-density lipoprotein (HDL) composition of patients with HIV-associated lipodystrophy (LDHIV). Twenty-four adult outpatients were enrolled to receive metformin (1700 mg/d) during 6 months, but 2 were lost to follow-up and 6 stopped the drug due to adverse events (gastrointestinal in 5, and excessive weight loss in 1). From the 16 subjects who completed the study, 69% were female. At baseline, 3 and 6 months, we assessed: weight, waist and hip circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
1
3
0
1
Order By: Relevance
“…AMPK activation may be a defense mechanism to counteract chronic inflammation and alteration in lipid metabolism. In agreement, treatment of patients infected with HIV with the antidiabetic drug metformin, an AMPK activator, has been associated with sustained benefits on markers of cardiovascular risk and improvement of lipoatrophy . Chronic comorbidities could explain levels of AMPK, which remained elevated over time during our follow‐up studies.…”
Section: Discussionsupporting
confidence: 69%
“…AMPK activation may be a defense mechanism to counteract chronic inflammation and alteration in lipid metabolism. In agreement, treatment of patients infected with HIV with the antidiabetic drug metformin, an AMPK activator, has been associated with sustained benefits on markers of cardiovascular risk and improvement of lipoatrophy . Chronic comorbidities could explain levels of AMPK, which remained elevated over time during our follow‐up studies.…”
Section: Discussionsupporting
confidence: 69%
“…Metformin is safe and generally well-tolerated; although gastrointestinal symptoms are common, they are mild and usually transient. However, not all subsequent studies have shown consistent improvements in insulin resistance, lipid profile, or anthropometric features 81,82 . Furthermore, metformin may worsen peripheral fat loss, and should therefore be used with caution in lipoatrophic patients 83 .…”
Section: Types Of Lipodystrophymentioning
confidence: 99%
“…It is prescribed for patients suffering from a variety of insulin-resistant and prediabetic states, including impaired glucose tolerance, obesity (Tankova et al , 2003; Rotella et al , 2006; Hirsch et al , 2009) and metabolic abnormalities associated with HIV disease (Hadigan et al , 2000; Johnson et al , 2005; Diehl et al , 2008). Furthermore, metformin is also used regulating anovulation, and induce and sustain pregnancy in polycystic-ovary syndrome patients (Jakubowicz et al , 2002; De Leo et al , 2006; Lilja and Mathiesen, 2006; Brassard et al , 2008).…”
Section: Introductionmentioning
confidence: 99%